Pengembangan Jaringan Komputer Universitas Surakarta Berdasarkan Perbandingan Protokol Routing Information Protokol (RIP) Dan Protokol Open Shortest Path First (OSPF) - Utomo, Prawido; Purnama, Bambang Eka (Speed - Indonesian Journal on Computer Science, 2014)
This research aims to evaluate Universitas Islam Negeri Sunan Kaljaga Library Information System which is focused on collage students satisfaction as user. Metode yang digunakan adalah dengan penyebaran kuisioner kepada mahasiswa yang diambil acak sebanyak 100 orang. Isi kuisioner mengacu kepada lima variabel pengukuran kepuasan pengguna yang dikembangkan oleh Doll dan Torkzadeh, yaitu Content, Accuracy, Format, Ease of Use dan Timeliness. the method of using questionaire through random-picked 100 students is used for the primary data. the questionaire refers to the five user satisfaction measurement variables which was developed by Doll and Torkzadeh: COntent, Accuracy, Format, Ease of Use, and Timeliness. The results of this research indicated that generally the five variables mentioned above are representations of user satisfaction. This research would hopefully become a recommendation to the management of UINSKs library to improve the quality of the LIS.